Capacity of Thymidylate Synthase and Dihydropyrimidine Dehydrogenase mRNA Expression to Predict Neoadjuvant Chemotherapy Response of 5fu Regimen in Advanced Colorectal Cancer: A Cross-Sectional Study - Tahiya, Elvida Christi Imelda; Lusikooy, Ronald Erasio; Patelongi, Ilhamjaya; Warsinggih, Warsinggih; Uwuratuw, Julianus Aboyaman; Islam, Andi Asadul; Faruk, Muhammad (Asian Pacific Journal of Cancer Biology, 2025)
Background: Chemotherapy is an important component of colorectal cancer treatment. Despite its success in inducing tumor cell death, chemotherapy has been constrained by resistance and adverse side effects. Therefore, predictive markers are required to ensure that the appropriate chemotherapy is administered based on the individual patient. This study aimed to correlate the mRNA expression of the TS and DPD genes with the tumor and CEA responses to the 5FU chemotherapy regimen. Methods: This was a cross-sectional study with a prognostic test design. Measurements of tumor mass and tissue sampling were done prior to chemotherapy. CT scans were performed to measure tumor size pre-chemotherapy and after two cycles of treatment with a lag time of three weeks. The mRNA expression of the TS and DPD genes was then evaluated in each group. Results: The mean value of the mRNA expression of the TS gene (9.555±1.693) showed an insignificant correlation with clinical response p=0.195 (p<0.05). However, the mean value of the mRNA expression of the DPD gene (7.461±1.088) was significantly correlated with clinical response p=0.003 (p<0.05). Conclusion: DPD mRNA can be considered a marker of chemotherapy responsiveness when choosing a chemotherapy regimen.